By simplifying
. This will result in a simplified version of
.
The Simplifying Algorithm is a wonderful way to simplify complex mathematics problems. It can be used to solve equations, convert fractions to decimals, and perform many other math operations. In this problem, the Simplifying Algorithm will help you reduce ![\[x - \frac{{23}}{{{x^2}}} - x - 20 - \frac{2}{5} - x\]](https://tex.z-dn.net/?f=%5C%5Bx%20-%20%5Cfrac%7B%7B23%7D%7D%7B%7B%7Bx%5E2%7D%7D%7D%20-%20x%20-%2020%20-%20%5Cfrac%7B2%7D%7B5%7D%20-%20x%5C%5D)
Since two opposites add up to 0, remove them from the expression.
![\[ - \frac{{23}}{{{x^2}}} - \frac{{102}}{5} - x\]](https://tex.z-dn.net/?f=%5C%5B%20-%20%5Cfrac%7B%7B23%7D%7D%7B%7B%7Bx%5E2%7D%7D%7D%20-%20%5Cfrac%7B%7B102%7D%7D%7B5%7D%20-%20x%5C%5D)
Write all numerators above the least common denominator 5x2
![\[ - \frac{{115 + 102{x^2} + 5{x^3}}}{{5{x^2}}}\]](https://tex.z-dn.net/?f=%5C%5B%20-%20%5Cfrac%7B%7B115%20%2B%20102%7Bx%5E2%7D%20%2B%205%7Bx%5E3%7D%7D%7D%7B%7B5%7Bx%5E2%7D%7D%7D%5C%5D)
Use the commutative property to reorder the terms so that constants on the left
![\[\frac{{ - 5{x^3} - 115 - 102{x^2}}}{{5{x^2}}}\]](https://tex.z-dn.net/?f=%5C%5B%5Cfrac%7B%7B%20-%205%7Bx%5E3%7D%20-%20115%20-%20102%7Bx%5E2%7D%7D%7D%7B%7B5%7Bx%5E2%7D%7D%7D%5C%5D)
Rearrange the terms
![\[\frac{{ - 5{x^3} - 102{x^2} - 115}}{{5{x^2}}}\]](https://tex.z-dn.net/?f=%5C%5B%5Cfrac%7B%7B%20-%205%7Bx%5E3%7D%20-%20102%7Bx%5E2%7D%20-%20115%7D%7D%7B%7B5%7Bx%5E2%7D%7D%7D%5C%5D)
By reording the terms
![\[ - \frac{{5{x^3} + 102{x^2} + 115}}{{5{x^2}}}\]](https://tex.z-dn.net/?f=%5C%5B%20-%20%5Cfrac%7B%7B5%7Bx%5E3%7D%20%2B%20102%7Bx%5E2%7D%20%2B%20115%7D%7D%7B%7B5%7Bx%5E2%7D%7D%7D%5C%5D)
Hence, by simplifying this equation, divide both numerator and denominator. This will result in a simplified version of
.
To learn more about simplifyication visit:
brainly.com/question/1542396
#SPJ1
Answer:
One and Four
Step-by-step explanation:
Answer:
62.5%
Step-by-step explanation:
Answer:
0.15
Step-by-step explanation:
<u>Independent Probabilities Formula</u>
P(A | B) = P(A) = P(A ∩ B) ÷ P(B)
P(A | B) = 0.25
P(A) = 0.25
P(B) = 0.6
If P(A) = P(A ∩ B) ÷ P(B)
P(A ∩ B) = P(A) × P(B)
P(A ∩ B) = 0.25 × 0.6
P(A ∩ B) = 0.15
This is an incomplete question, the image is shown below.
Answer : The fraction empty container is, ![\frac{7}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B12%7D)
Step-by-step explanation :
As we are given that:
The capacity of container = 60 mL
In the given figure, the container is filled with 25 mL.
That means,
60 - 25 = 35 mL container is empty.
Now we have to calculate the fraction of it is empty.
The fraction of it is empty = ![\frac{\text{Capacity of empty container}}{\text{Total capacity of container}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Ctext%7BCapacity%20of%20empty%20container%7D%7D%7B%5Ctext%7BTotal%20capacity%20of%20container%7D%7D)
The fraction of it is empty = ![\frac{35mL}{60mL}](https://tex.z-dn.net/?f=%5Cfrac%7B35mL%7D%7B60mL%7D)
The fraction of it is empty = ![\frac{7}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B12%7D)
Therefore, the fraction empty container is, ![\frac{7}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B7%7D%7B12%7D)